2019
DOI: 10.1186/s12879-019-3960-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physical exercises on inflammatory biomarkers and cardiopulmonary function in patients living with HIV: a systematic review with meta-analysis

Abstract: Background Pro-inflammatory cytokines expressed in human immune deficiency virus (HIV) infection, may induce oxidative stress likely to compromise the patency of the airways or damage the lung tissues/cardiac function. However, physical (aerobic and/or resistance) exercise-induced release of heat shock protein, immune function alteration or reduced tissue hypoxia, have been highlighted as possible mechanisms by which increasing physical activity may reduce plasma pro-inflammatory cytokines in unin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 72 publications
3
17
0
Order By: Relevance
“…We observed a significant reduction in the levels of TNF-α among the exercisers compared with the nonexercisers in this study. However, the IL-6 levels did not differ significantly which is similar to the findings from other studies that showed no significant impact of exercise training on IL-6 levels (20). It has been observed that although ART itself reduces the levels of IL-6, IFN-γ, and IL-10 to the levels seen in uninfected controls, a similar effect is not observed in the case of TNF-α and the levels of which remain elevated even after prolonged ART (3,34,37).…”
Section: Discussionsupporting
confidence: 89%
“…We observed a significant reduction in the levels of TNF-α among the exercisers compared with the nonexercisers in this study. However, the IL-6 levels did not differ significantly which is similar to the findings from other studies that showed no significant impact of exercise training on IL-6 levels (20). It has been observed that although ART itself reduces the levels of IL-6, IFN-γ, and IL-10 to the levels seen in uninfected controls, a similar effect is not observed in the case of TNF-α and the levels of which remain elevated even after prolonged ART (3,34,37).…”
Section: Discussionsupporting
confidence: 89%
“…The lack of reliable evidence to guide practice in this regard is an important gap in the literature because physical exercise has been found to minimize or improve co-morbidities associated with HIV/AIDS. Physical exercises improve cardiovascular fitness, muscle strength, lean body mass, instability of fat metabolism, increase bone mineral density, reduce risk of fracture and invariably enhance the quality of life in people living with HIV/AIDS [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exercise can reduce the risk of multimorbidity and improve health outcomes for adults living with HIV [9][10][11]. Systematic review evidence demonstrated that engaging in aerobic, resistive or combined aerobic and resistive exercise at least three times per week can improve cardiorespiratory fitness, strength and quality of life outcomes among adults living with HIV [12][13][14].…”
Section: Introductionmentioning
confidence: 99%